Selection of Newly Identified Growth-Promoting Archaea Haloferax Species With a Potential Action on Cobalt Resistance in Maize Plants - Selim, Samy; Akhtar, Nosheen; Hagagy, Nashwa; Alanazi, Awadh; Warrad, Mona; El Azab, Eman; Elamir, Mohammed Yagoub Mohammed; Al-Sanea, Mohammad M.; Jaouni, Soad K. Al; Abdel-Mawgoud, Mohamed; Shah, Anis Ali; Abdelgawad, Hamada (Frontiers in Plant Science, 2022)
Soil contamination with cobalt induces toxic impact on plant growth and production. On the other hand, plants Growth Promoting microorganisms are effectively used for improving plant growth under a range of stress conditions. To this end, unclassified haloarchaeal species strain NRS_31 (OL912833), belong to Haloferax, for the first time, was isolated, identified and applied to mitigate cobalt phytotoxic effect on maize plants. Cobalt contamination in soil induced cobalt accumulation in maize leaves. Consequentially, it inhibited maize growth and photosynthetic efficiency, and induced tissue oxidative damages. On the other hand, pre-inoculation with haloarchaeal species significantly reduced cobalt uptake, and mitigated the cobalt toxicity. Induced photosynthesis improved sugar metabolism which allocates more carbon to defense against cobalt stress. Concomitantly, the biosynthetic key enzymes involved in sucrose (sucrose-P-synthase and invertases) and proline (pyrroline-5- carboxylate synthetase (P5CS), pyrroline-5-carboxylate reductase (P5CR)) biosynthesis were significantly increased to maintain plant osmotic potential. In addition to their osmoregulation potential, soluble sugars and proline can contribute to maintain ROS hemostatus. Moreover, Maize leaves managed their oxidative homeostasis by increasing the production of antioxidant metabolites (such as phenolics and tocopherols) and increasing the activity of ROS-scavenging enzymes (such as POX, CAT, SOD, and enzymes involved in the AsA/GSH cycle). Inside plant tissue, to overcome heavy cobalt toxicity, maize plants increased the synthesize of heavy metal-binding ligands (metallothionein, phytochelatins), and the metal detoxifying enzymes (glutathione s transferase). Overall, improved ROS homeostasis and improved osmoregulation and cobalt detoxification systems were the bases underlie the cobalt oxidative stress mitigating impact of Haloarchaeal treatment.